On the Entanglements of Heritage—Afterword to the Special Issue Sacred Heritage: Religions and Material Culture - Coleman, Simon (Religions, 2025)
A sign of a productive sub-field is that it can develop ramifying links with other areas of research whilst retaining the distinctiveness that first brought it into being [...]